DINASTI POLITIK: BASIS POLITIK DAN KEPUASAN PUBLIK - Haliim, Wimmy; Hakim, Andy Ilman (JPP (Jurnal Politik Profetik), 2020)
The opening of political access in a country that was going through a period of democratic transition gave rise to "little kings" through the practice of political dynasties in some regions. They fill the local political space by restructuring patronage networks and strengthening their social, economic and political bases in order to maintain their power. This kind of dynastic political practice generates negative sentiments towards the performance of the bureaucracy as the public policy tend to be beneficial for a particular political family. The research focuses on the impact of the Sutrisno family's political dynasty through the bureaucracy on the level of community satisfaction towards the performance and achievements of their programs. Given the impact of the Sutrisno family's dynastic political practices, some of them show an anomaly. The findings illustrate the high level of public satisfaction with the performance of the bureaucracy in the health, education, and economy sectors. Apart from the fact that the Sutrisno family dynasty was politically established and had consequences for control of the bureaucracy, the social base of the Sutrisno family network also played an important role in increasing public acceptance of bureaucratic work programs in various fields.